Causality Analysis of Inflation and Economic Growth Using the Error Correction Model (ECM) - Ella Silvia; Netty Vera Sihotang; Demita Sihotang (Institute of Accounting Research and Novation (IARN), 2023)
This research delves into the relationship between inflation and economic growth, employing the Error Correction Model (ECM) to examine their dynamic interplay. Inflation and economic growth stand as pivotal indicators of economic health, influencing policy decisions, market behaviors, and overall economic stability. Through empirical analysis, this study seeks to unravel the complexities of their relationship to guide policymakers and stakeholders in navigating the economic landscape. Utilizing the ECM, this research investigates the directional relationship between inflation and economic growth, analyzing coefficients and their statistical significance. The findings offer insights into the causal dynamics and the implications for economic policies and market behaviors. The significance of understanding this relationship is evident in the formulation of nuanced economic policies. These findings have implications for monetary and fiscal policies, guiding policymakers in managing inflation while fostering economic growth. Investors, businesses, and financial institutions can leverage this understanding to make informed decisions and manage risks associated with economic fluctuations. The research underlines the importance of adaptable policies that respond to the contextual nuances of the relationship between inflation and economic growth. In conclusion, the research elucidates the vital role that empirical analysis plays in guiding economic policies and shaping economic landscapes. Understanding the intricate relationship between inflation and economic growth offers a roadmap for policymakers, investors, and researchers to navigate the challenges and opportunities within the ever-evolving economic environment